2015
DOI: 10.1007/s00464-015-4327-2
|View full text |Cite
|
Sign up to set email alerts
|

Robotic approaches may offer benefit in colorectal procedures, more controversial in other areas: a review of 168,248 cases

Abstract: Robotic approaches may facilitate safer adoption of minimally invasive approaches in areas where penetrance of conventional laparoscopy is low, such as in colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“… 14 So far, robotic colorectal surgery has been shown to have decreased complications and shorter lengths of stay, compared with conventional laparoscopy. 15 …”
Section: Resultsmentioning
confidence: 99%
“… 14 So far, robotic colorectal surgery has been shown to have decreased complications and shorter lengths of stay, compared with conventional laparoscopy. 15 …”
Section: Resultsmentioning
confidence: 99%
“…A number of previously published studies on robotic surgery including hysterectomy[ 18 ] prostatectomy[ 19 ], and cholecystectomy[ 20 ], showed that operation time was prolonged. The analysis of surgical outcomes showed that operation time was significantly longer in the RADP group.…”
Section: Discussionmentioning
confidence: 99%
“…However, current evidence of clear clinical benefit over laparoscopy is lacking for most procedures. Robotic surgery may be advantageous for more complex cases in high-volume centers [23] and may prove beneficial in increasing minimally invasive surgery in areas of low laparoscopic penetrance, such as colorectal surgery [24]. A procedure that cannot be otherwise routinely performed in a minimally invasive fashion, but can be accomplished using the robotic platform, is an ideal candidate for the application of this emerging technology.…”
Section: Discussionmentioning
confidence: 99%